Tribeca Belfast and the on-screen regeneration of Northern Ireland. (1st March 2020) - Baker, Stephen
This article looks at media representations of the projected regeneration of Northern Ireland, paying particular attention to a recent promotional film made to elicit support for the redevelopment of a part of Belfast's city centre. Commissioned by Castlebrooke Investments, 'Tribeca Belfast' offers a future prospectus of the city that is as superficial as it is bland. It is, however, illustrative of two influential ideas and strategies that took flight at the end of the Cold War and the 'triumph of capitalism'. One seeks peace through the application of neo-liberal nostrums; the other combines brand theory with state-craft in pursuit of global competitiveness. Both propose models of citizenship that are politically benign, either preferring middle class solipsism or demanding brand loyalty. In Castlebrooke's projection of a future Belfast, this translates into a city peopled by a mobile professional class, waited upon and entertained by servile locals. But such a sterile vision is inimical to building peace and political progress because it underestimates and downplays the significance of marginalized groups who through their activism and expressions of solidarity can lay better claim to the 'heart and soul' of Belfast evoked by Castlebrooke.